Biogas cook stoves for healthy and sustainable diets? A case study in Southern India - Tal Lee Anderman; Ruth S DeFries; Stephen A Wood; Stephen A Wood; Roseline eRemans; Roseline eRemans; Richie eAhuja; Shujayath E Ulla (Frontiers in Nutrition, 2015)
Alternative cook stoves that replace solid fuels with cleaner energy sources, such as biogas, are gaining popularity in low-income settings across Asia, Africa and South America. Published research on these technologies focuses on their potential to reduce indoor air pollution and improve respiratory health. Effects on other cooking related aspects, such as diets and women’s time management, are less understood. In this study in southern India, we investigate if using biogas cook stoves alters household diets and women’s time management. We compare treatment households who are supplied with a biogas cook stove with comparison households who do not have access to these stoves, while controlling for several socio-economic factors. We find that diets of treatment households are more diverse than diets of comparison households. In addition, women from treatment households spend on average 40 minutes less cooking and 70 minutes less collecting firewood per day than women in comparison households. This study illustrates that alongside known benefits for respiratory health, using alternative cook stoves may benefit household diets and free up women’s time. To inform development investments and ensure these co-benefits, we argue that multiple dimensions of sustainability should be considered in evaluating the impact of alternative cook stoves.